MAPPING AND DETECTING LAND USE LAND COVER (LULC) CHANGES DYNAMICS OF PER-URBAN SPACES IN CONSTANTINE CONTEMPORARY STATES (NORTHEAST OF ALGERIA) A GEO-SPATIAL METHODS BY USING GIS, REMOTE SENSING, LCM AND GEE PLATFORM FROM 1984 TO 2020 - Abdi Nidal; Allaoua Boulehouache (International Journal of Innovative Technologies in Social Science, 2024)
Cities through his urbanizations strongly distort the land use to divergent spaces and casing a change in the natural land cover. This impact makes it necessary to provide municipalities with land use maps and information relating to their condition and dynamics. This study aims to map changes and effects of human activities in a Per-urban space area of Constantine contemporary states CCS ( North East of Algeria) .Within sixty tree years and experiment the suitability of Google earth Engine platform data’s and remote sensing techniques for lands protection as an effort to preserve it following urban planning. For that reason, a multi temporal satellite Landsat 5TM (in 1984, 1991, 1998, 2005, 2012) and Landsat 8 OLI (in 2020) was investigated from 1984 to 2020 (5 periods) and a spatial resolution of 30 meters. a supervised classification with random forest algorithm with accuracy test by means of the confusion matrix and kappa index are applied. Moreover, local ground information allowed uncovering the dynamic of land-cover shape in the study area. The results of LUCL class changes in Constantine states North East of Algeria Region from 1984 to 2020 indicates that the agricultural land in per-urban spaces has the potential to be urbanized. In addition, the water land, forests land and built up land classes are increasing respectively by +0.23%, +2.06% and +57.98% in the period study. Unlike, the agricultural land and bare land classes wich are experiencing a remarquable reduction respectively by -29.70% and -30.58% over the whole study area. Where the main causes are: the massive rural exodus; population growth, the increasing demand for constructive land and type of agriculture practiced by the population.These results could serve as a basis for defining priority intervention areas for the restoration of degraded areas and the management of agricultural and natural per urban spaces.